DAMPAK MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS IV PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Caca Angwar Maulana Yusuf; Agus Muharam; atep Lesmana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the impact of the Discovery Learning model on improving the critical thinking skills of fourth-grade elementary school students in Integrated Science and Social Studies (IPAS). The study was motivated by the low level of students' critical thinking skills caused by teacher-centered learning, which limited students' opportunities to actively analyze, investigate, and solve problems. This research employed a quantitative approach using a Pre-Experimental Design with a One-Group Pretest–Posttest Design. The research participants consisted of fourth-grade students at SDN Giriwangi. Data were collected through critical thinking tests administered before and after the implementation of the Discovery Learning model. The collected data were analyzed using descriptive statistics, prerequisite tests, and hypothesis testing to determine the effect of the treatment. The findings indicate that students' critical thinking skills improved after participating in learning activities based on the Discovery Learning model. Students demonstrated better abilities in interpreting information, analyzing problems, evaluating evidence, drawing logical conclusions, and explaining their ideas systematically. The learning process also encouraged students to become more active in observing, discussing, investigating, and constructing knowledge independently. These findings support Bruner's constructivist theory, which emphasizes that meaningful learning occurs when students discover concepts through direct experience. Therefore, the Discovery Learning model can be considered an effective learning alternative for improving elementary school students' critical thinking skills in IPAS learning.